An Introduction to the Special Issue on "Disasters, Religion, and Spirituality" - Davis, Edward B. (Journal of psychology and christianity, 2018)
The article discusses various reports published with the issue which includes study of survivors of the 2016 Louisiana floods, qualitative study of adult survivors of the 2010 Haiti earthquake and study of disaster spiritual and emotional care providers.